MORPHOLOGICAL CHANGES OF RATS` SPLEEN IN THE CONDITION OF CELLULAR DEHYDRATATION ON BACKGROUND OF POSTTRAUMATIC REGENERATION OF TIBIA - Васько, Л.В.; Kiptenko, L.I.; Gorpinskaya, O.M.; Pryhodko, O.O. (World of Medicine and Biology, 2014)
Research of internal organs influenced by the hyperosmolar cellural dehydration moderate severity against the background of posttraumatic regeneration of the tibia was made. Studied the spleen of adult rats. In the studied tissues of the spleen the most pronounced changes observed in the last stages of the experiment (21 days) and characterized by decreasing the sizes of structural elements of the organ, violation of architectonics and pronounced changes in the microcirculation.
Keywords: spleen; dehydration; posttraumatic regeneration